Production of Different Biochemicals by Paenibacillus polymyxa DSM 742 From Pretreated Brewers’ Spent Grains - Didak Ljubas, Blanka; Novak, Mario; Trontel, Antonija; Rajković, Ana; Kelemen, Zora; Marđetko, Nenad; Grubišić, Marina; Pavlečić, Mladen; Tominac, Vlatka Petravić; Šantek, Božidar (Frontiers in Microbiology, 2022)
Brewers` spent grains (BSG) is a byproduct of brewing industry that is mainly used as feedstock, or it has to be disposed according to regulations. Due to high content of glucose and xylose, after pretreatment and hydrolysis, it can be used as a main carbohydrate source for cultivation of microorganisms for production of biofuels or biochemicals like 2,3-butanediol or lactic acid. 2,3-butanediol has applications in pharmaceutical or chemical industry as a precursor for varnishes and paints or in food industry as an aroma compound. So far, Klebsiella pneumoniae, Serratia marcescens, Clostridium sp., Enterobacter aerogenes are being used and investigated in different bioprocesses aimed at the production of 2,3-butanediol. The main drawback is bacterial pathogenicity which complicates all production steps in laboratory, pilot and industrial scale. In our study, a gram-positive GRAS bacterium Paenibacillus polymyxa DSM 742 was used for the production of 2,3-butanediol. Since this strain is very poorly described in literature, bacterium cultivation was performed in media with different glucose and/or xylose concentration ranges. The highest 2.3-butanediol concentration of 18.61 g L-1 was achieved in medium with 70 g L-1 of glucose during 40 h of fermentation. In contrary, during bacterium cultivation in xylose containing medium there was not significant 2,3-butanediol production. In next stage, BSG hydrolysates were used for bacterial cultivation. P. polymyxa DSM742 cultivated in the liquid phase of pre-treated BSG produced very low 2.3-butanediol and ethanol concentrations. Therefore, this BSG hydrolysate has to be detoxified in order to remove bacterial growth inhibitors. After detoxification, bacterium cultivation resulted in 30 g L-1 of lactic acid, while production of 2,3-butanediol was negligible. The solid phase of pre-treated BSG was also used for bacterium cultivation after its hydrolysis by commercial enzymes. In these cultivations, P. polymyxa DSM 742 produced 9.8 g L-1 of 2,3-butanediol and 3.93 g L-1 of ethanol. On the basis of obtained results it can be concluded that different experimental set-ups give the possibility of directing the metabolism of P. polymyxa DSM 742 towards the production of either 2,3-butanediol and ethanol or lactic acid.